Beta-galactosidase-responsive synthetic biomarker for targeted tumor detection. Issue 83 (2nd October 2018) - Nishihara, Tatsuya; Kuno, Satoshi; Nonaka, Hiroshi; Tabata, Sho; Saito, Natsumi; Fukuda, Shinji; Tomita, Masaru; Sando, Shinsuke; Soga, Tomoyoshi
Abstract : Tumor biomarkers are highly desirable for the screening of patients with a risk of tumor development and progression. Abstract : Tumor biomarkers are highly desirable for the screening of patients with a risk of tumor development and progression. Here, we report a beta-galactosidase (β-gal)-responsive acetaminophen (β-GR-APAP) as a synthetic plasma biomarker for targeted tumor detection. Tumor β-gal labeling via the recognition of tumor-related antigen enabled the detection of a tumor using β-GR-APAP.